PERANAN GURU DALAM MENGEMBANGKAN KARAKTER SISWA MELALUI PROGRAM UNGGULAN SEKOLAH DI SMP NEGERI 1 BANGLI - Putu Sri Wijnyanawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Teachers play an important role in education, in developing students' cognitive (knowledge), affective (attitude), and psychomotor (skills) aspects. In addition, the teacher is also a role model for students. Teachers must be able to be an example where before directing students to behave well. One of the programs at SMP Negeri 1 Bangli that can be implemented to develop student character is the School Excellence Program. This study aims to obtain accurate information and an objective description of the role of teachers in developing student character through the School Excellence Program. The data collection methods used are: observation, interview, literature study and documentation study. The data that has been collected is analyzed by descriptive qualitative analysis method. The results showed (1) The role of teachers in developing student character through the school's flagship program at SMP Negeri 1 Bangli, namely: (1) the teacher as a role model. (2) teacher as an inspirer. (3) teacher as a motivator. (4) teacher as a dynamizer. (5) teacher as an evaluator. (2) Obstacles and efforts made in developing student character at SMP Negeri 1 Bangli. The obstacles encountered are different student characters, lack of student awareness, Lack of parental attention to students and facilities and infrastructure. Efforts made by the teachers are increasing the role of teachers and coordinate with parents. (3) The implications of implementing the school's flagship program on the development of student character in SMP Negeri 1 Bangli are: the development of students' character, increasing students' awareness to carry out their religious teachings, increasing students' concern for others, increasing students' concern for the environment, increasing students' interest in reading and self-confidence and creating a positive school culture.